Levels of copper in Nile tilapia from Brazil - Neves, Renato C. F. [UNESP]; Moraes, Paula M. [UNESP]; Ferrari, Jeisson E. M. [UNESP]; Lima, Paula M. [UNESP]; Santos, Felipe A. [UNESP]; de Castro, Gustavo Rocha [UNESP]; Barros, Margarida M. [UNESP]; Padilha, Pedro M. [UNESP] (Taylor & Francis Ltd, 2011)
The purpose of this work was to determine the concentration of copper in samples of farmed Nile tilapia (Oreochromis niloticus L.) fillets purchased in the city of Botucatu (São Paulo, Brazil) and in fillet and liver samples of Tilapia fed diets supplemented with different concentrations of Cu from the Laboratory of Aquatic Organism Nutrition/FMVZ-UNESP (Botucatu, Brazil). The fillet samples were prepared by lyophilisation and cryogenic grinding into particles smaller than 60 mm, and copper was extracted ultrasonically using 0.10 mol l(-1) HCl as extraction solution. Copper determination was performed by graphite furnace atomic absorption spectrometry (GFAAS) with optimised temperatures of drying, pyrolysis, atomisation and cleaning. Palladium nitrate was injected into the samples as a chemical modifier and tungsten as a permanent modifier. Copper concentrations of 0.70-1.60mg kg(-1) were found, which are in line with Brazilian regulations. The accuracy and precision of the copper concentrations determined in this study were evaluated using certified standard Lake Michigan fish tissue (NIST SRM 1947)
Keywords: copper; feeding; animal feed; fish; mineral